Resequencing of cv CRI‐12 family reveals haplotype block inheritance and recombination of agronomically important genes in artificial selection. Issue 5 (3rd December 2018) - Lu, Xuke; Fu, Xiaoqiong; Wang, Delong; Wang, Junyi; Chen, Xiugui; Hao, Meirong; Wang, Junjuan; Gervers, Kyle A.; Guo, Lixue; Wang, Shuai; Yin, Zujun; Fan, Weili; et al.
Summary: Although efforts have been taken to exploit diversity for yield and quality improvements, limited progress on using beneficial alleles in domesticated and undomesticated cotton varieties is limited. Given the complexity and limited amount of genomic information since the completion of four cotton genomes, characterizing significant variations and haplotype block inheritance under artificial selection has been challenging. Here we sequenced Gossypium hirsutum L. cv CRI‐12 (the cotton variety with the largest acreage in China), its parental cultivars, and progeny cultivars, which were bred by the different institutes in China. In total, 3.3 million SNPs were identified and 118, 126 and 176 genes were remarkably correlated with Verticillium wilt, salinity and drought tolerance in CRI‐12, respectively. Transcriptome‐wide analyses of gene expression, and functional annotations, have provided support for the identification of genes tied to these tolerances. We totally discovered 58 116 haplotype blocks, among which 23 752 may be inherited and 1029 may be recombined under artificial selection. This survey of genetic diversity identified loci that may have been subject to artificial selection and documented the haplotype block inheritance and recombination, shedding light on the genetic mechanism of artificial selection and guiding breeding efforts for the genetic improvement of cotton.